SOSIALISASI PENTINGNYA SANITASI LINGKUNGAN DAN GIZI BAGI SISWA-SISWI SDN 1 BUGEMAN KABUPATEN SITUBONDO - Kartika Sari, Vega; Abraham, Natanael Firstly; Aszhuraini, Aszhuraini; Rofi’ah, Rizka Febby; Mahendra, Aldi; Ferdiansyah, Mohammad Feri; Christanty, Natasya Rahel; Basuki, Basuki; Kusumawati, Shinta (Department of Agronomy, Faculty of Agriculture, University of Jember, 2026)
The nutritional status of children in Indonesia needs serious attention because of the significant prevalence of malnutrition, stunting, and wasting in several regions, including Situbondo Regency. Bugeman Village, Kendit District, has a score of 37.21 for clean water and sanitation, and 33.33 for hunger-free. This service aimed to educate school children about the importance of sanitation in an effort to improve nutritional status. The target of this activity was elementary school students in grades 5 and 6 of SDN 1 Bugeman, Situbondo Regency. The pre-test and post-test results of 43 elementary school students who had participated in the socialization showed an increase of 40.466 points. This significant change was expected to have a positive impact on students understanding of the importance of sanitation and balanced nutrition. The knowledge provided would be more meaningful if it is supported by concrete steps in improving sanitation, nutrition education, and developing health facilities.